(untitled) (Handbook of Treatment Algorithms for Medical and Pharmacy Students, 2025)
Author Mrs. Nagalakshmi Konarachapalle, Associate Professor, Department of Pharmaceutical Chemistry, Annamacharya College of Pharmacy, Rajampet, Andhra Pradesh, India Abstract Neurological treatment algorithms are highly time-sensitive and etiology-specific, aimed at preventing neuronal death, controlling abnormal signaling, or slowing progressive degeneration. The algorithm for acute ischemic stroke is one of emergency reperfusion, stratified by time from onset, using intravenous thrombolysis (alteplase) within 4.5 hours or mechanical thrombectomy up to 24 hours for large vessel occlusions. The epilepsy algorithm is stratified by seizure type (focal vs. generalized), with the goal of achieving seizure freedom via first-line monotherapy (e.g., levetiracetam, valproate); failure leads to a stepwise trial of alternative or adjunctive agents. The status epilepticus algorithm is a rapid, timed protocol beginning with benzodiazepines. Multiple sclerosis management is bifurcated: acute relapses are treated with high-dose corticosteroids, while the long-term algorithm involves early initiation of disease-modifying therapies (DMTs), selected based on an "escalation" vs. "induction" strategy. Parkinson's disease follows a symptomatic algorithm, initiating therapy with MAO-B inhibitors or dopamine agonists in younger patients, and progressing to levodopa/carbidopa as the gold standard for motor control, with adjunctive therapies to manage motor fluctuations. Alzheimer's disease management is currently symptomatic, using cholinesterase inhibitors (e.g., donepezil) for mild-to-moderate stages and memantine for moderate-to-severe disease to modestly improve cognition and function Keywords: Neurological Algorithms, Stroke, Epilepsy, Multiple Sclerosis, Parkinson's Disease, Alzheimer's Disease VIEW PDF